Polymers and their Nanostructures in Therapeutic Delivery: An Overview - Ghimire, Yubaraj; Bhattarai, Ajaya; De, Ranjit (Journal of Vishwa Adarsha College, 2024)
Polymers and nanoparticles have recently played a vital role in targeted therapeutic delivery. From the beginning of the 20th century, nanomedicines have tremendously grown, driven by the enhancement in chemical engineering. These days, the rational design of polymers and nanoparticles built to perform diverse biological functions and customization for a given drug is the foundation for modern advancements in therapeutic delivery. This review mainly highlights the different types of polymers and their nanocarriers used in targeted drug delivery and their prospective applications and discusses the potential barriers in the field. The most recent advancements in polymers that may direct intracellular distribution are highlighted in this review as the areas pushing the boundaries of medication delivery.